IMPLEMENTASI KEBIJAKAN KURIKULUM MERDEKA DI SMP NEGERI 1 KARANGDADAP - Erlin Sofiyanti; Inayah Inayah; Nurkolis Nurkolis (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to assess how the Independent Curriculum is implemented in SMP Negeri 1 Karangdadap and how it affects the educational process. Data were collected using a qualitative research approach that included document analysis, observation, and interviews. The respondents were teachers, students, and the principal. The findings of the study indicate that increasing student interest in learning is a successful outcome of the implementation of the Independent Curriculum. Students are allowed to choose the resources and teaching strategies that best suit their interests, which encourages originality and creativity. However, there are still some problems such as lack of infrastructure and facilities, and lack of training for teachers. Based on the results of the study, although the Independent Curriculum of SMP Negeri 1 Karangdadap has shown encouraging developments, more facilities and teacher training are still needed to maximize the implementation of the curriculum. The Independent Curriculum can be a useful tool to improve teaching standards in the classroom with appropriate adjustments.